Application of ionic‐liquid‐supported magnetic dispersive solid‐phase microextraction for the determination of acaricides in fruit juice samples. Issue 19 (1st September 2013) - Zhang, Jiaheng; Li, Min; Li, Yubo; Li, Zongyang; Wang, Fenfen; Li, Qiu; Zhou, Wenfeng; Lu, Runhua; Gao, Haixiang
<x xml:space="preserve">Abstract</x> In this study, ionic liquid (IL) supported magnetic dispersive solid‐phase microextraction was developed and a systematic investigation was conducted on imidazolium ILs for their extraction performance. This nano‐based pretreatment procedure was then applied for the determination of acaricides in fruit juice samples for the first time. A feature of this technique is that the commonly laborious chemical modification of magnetic nanoparticles (MNPs) was skillfully circumvented. Because of the combination of ILs, dispersive liquid–liquid microextraction, and dispersive MNP solid‐phase microextraction, the extraction efficiency can be significantly improved using commercial MNPs. Parameters of the extraction method were investigated by one‐factor‐at‐a‐time approach. The optimal experimental conditions were as follows: emulsification for 2 min by sonication with the addition of 50 μL [C6MIM][NTf2] in the dispersive liquid–liquid microextraction step and vortexing for 90 s after adding 40 mg spherical barium ferrite nanoparticles (20 nm). The desorption time was 2 min. Good linearity (0.5–500 ng/mL) and detection limits within the range of 0.05–0.53 ng/mL were achieved. The application of the proposed method was demonstrated by the analysis of real fruit juice samples, in which recoveries between 85.1 and 99.6% were obtained.